Gene expression studies in bacterial leaf blight resistant and susceptible rice (Oryza sativa) lines - PRAVEEN, N M; RAMANATHAN, A; BHARANIDEEPAN, A; MANASA, R; MONISHA, S; NAKKEERAN, S; KUMARAVADIVEL, N (The Indian Journal of Agricultural Sciences, 2020)
Bacterial leaf blight of rice is a major constraint in tumbling productivity of the crop which shows the precarious nature of the disease. Host resistance is an effective strategy for the management of bacterial leaf blight disease over the cultural, chemical and biological management methods. Glass house and field studies were performed during 2017–19 at Paddy Breeding Station, TNAU, Coimbatore and also the molecular laboratory facility at Department of Plant Pathology was utilized. The objective of the study was to perform gene expression studies resistance genes (Xa21, xa5, xa13 genes) and defense genes (LOX and PAL) in bacterial leaf blight resistance (IRBB 60) and susceptible rice line (TN1) after application of Xanthomonas oryzae. pv. oryzae and/or riboflavin. Genotyping of IRBB 60 which showed lowest lesion length validated the presence of Xa21, xa5 and xa13 resistance genes using corresponding gene specific primers. Application of riboflavin (0.5mM) along with the Xanthomonas oryzae. pv. oryzae suspension resulted in the highest expression level of these R genes and defense genes except xa13 gene which showed its highest expression level with the inoculation of Xoo alone. Expression of Xa13 gene was meagre with the treatment of riboflavin where rest of the gene expression was noticeably enhanced when compared to the control. In brief, study performed showed that application of abiotic agent (Riboflavin) enhanced the gene expression of both the resistance and defense gene in rice line when compared to the susceptible variety.